Signal-receiving UAV Positioning Model Based on Geometric Analysis - Li, Yinfeng; Wang, Qisen; Gu, Yongcheng; Zhou, Xintong; Song, Chenming (International Journal of Computer Science and Information Technology, 2024)
A drone is an aerial vehicle without a pilot or controller that is remotely controlled using aerodynamics to fulfil a designated task under certain circumstances. With the encouragement and support of national policies, the development of China's UAV industry has a good prospect. In real life, location information is the key information for UAVs to accurately complete operations and realise mission requirements, and the importance of its accurate positioning is self-evident. For the UAV localisation model, the bias-free localisation model is established first, and then the localisation model in the case of bias is solved on this basis. When there is a deviation in the received signal UAV, the UAV may be located outside the circle, on the circle, and inside the circle. Specifically divided into four scenarios, see Figure 1-4. (Analysed: outside the circle: θ1’θ1; circle on the left: θ2>θ2’, right: θ2